Phosphorus and Ammonium Ions Removal by Using The Microalgae Dunaliella salina - Wike Ayu Eka Putri; Moh. Muhaemin Moh. Muhaemin (Faculty of Mathtmatics and Natural Sciences, 2010)
Biological treatment for industrial effluent was performed in laboratory scale experiment by using marine microalgae Dunaliella salina. The dark colored wastewater, containing high level of organic matter and low pH which may prevent microalgae growth. The research showed that within 5 days of incubation in the wastewater, D. salina grew from 3×106 to 1.5×107 cell/mL. D. salina reduced approximately phosphorus (29%), and ammonium ionic (68%). The research demonstrated the possibility of using marine microalgae for bioremediation treatment of industrial wastewater, specifically.